Literature Review: Analisis Hubungan Pemakaian Bedong pada Bayi Baru Lahir terhadap Kesehatan Bayi di Indonesia - Romadlona, Nohan Arum; Rifanti, Dinda Putri; Hartanto, Maria Kireina; Ummah, Mazroatul Khoiroh; Sucita, Ni Made Dwi Astini; Aulia, Raveena Amira; Amelia, Talitha; Novembriani, Rizqie Putri (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
Baby swaddling or baby wrapping is an Indonesian custom practiced on newborn babies with the aim of providing a sense of comfort, warmth, and protection. Swaddling also has a negative impact on the baby's motor development where at the time of swaddling the baby cannot perform movement activities freely and get motion stimulation from the environment. The purpose of this study was to determine the relationship between the use of swaddling in newborns and infant health in Indonesia. This research method is to use the literature review method by analyzing, summarizing and comparing one research with another from related journal sources that can be accessed on Google Scholar. From the results of the analysis through literature review, it was found that swaddling has positive and negative effects on infants. Among the positive effects are to help increase the baby's body temperature, improve sleep quality, and make the baby feel comfortable, while the negative effect is to slow down gross motor development in infants.